Determinants of Poverty in East Java after the Covid-19 Pandemic - Purwanti, Dyah; Budiantono, Sigit; Nurhidayati, Nurhidayati; Sihombing, Pardomuan Robinson; Arsani, Ade Marsinta (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 2, Agustus 2023 (pp.187-360), 2023)
The Covid-19 pandemic has significantly impacted the economy both nationally and nationally.    Economic activity slowed down, many businesses closed their businesses, and there was an increase in the poor.   The government is conducting fiscal interventions to overcome the impact of the pandemic both on supply and demand. The intervention is expected to keep the economy growing despite being thin. East Java Province had achievements in reducing poverty until the end of 2019; after the pandemic, poverty increased significantly at the end of 2021. This condition is challenging for the Provincial Government and the City / Regency Government in East Java. Therefore, this study analyzes the determinants of poverty in East Java after the pandemic. Data was sourced from the Statistic Indonesia of East Java for 2018-2021. Using a regression of panel data (fixed effect model), we found that the human development index reduced poverty. On the contrary, the Covid pandemic, this ratio, and economic growth positively impact poverty. The implications of the findings suggest the need for comprehensive economic and macro-social policies so that the poverty rate in East Java can be reduced.